Spatio-temporal Variations in Sea-Surface-Temperature and Salinity Level in the Northern Bay of Bengal between 2016 and 2020 (Journal of Science and Technology Research, 2026)
The Bay of Bengal (BoB) is a continuum receiving numerous major rivers including  the Mahanadi, Godavari, Krishna, Kaveri, Ganges, Brahmaputra, Meghna, and many  more others. The river outputs are greatly impacted by the dynamic circulation system  along the shelf. As anticipated, the freshwater influx from rivers leads to lower salinities  and shallower mixed layers. Yet, the effect of this extra freshwater input into the bay is  unexpectedly complex. Meanwhile, the considerable freshwater flow from these rivers  transforms the density and dynamic height of the receiving seas, potentially influencing  primary productivity in the northern BoB. Various observational, reanalysis, and  satellite datasets—such as river discharge, temperature, salinity, density, and chlorophyll  concentration—are analyzed using heterogeneous correlation methods. The data  sources include the Copernicus Marine Environment Monitoring Service and ERAInterim.  It highlights that Classic estuarine two-layer circulation during monsoonal  period is one of the significant consequences of river plume influence on continental  shelf. Coriolis force, which is governed by earth rotation, monsoonal effect and buoyant  river plumes are what makes this discovery so significant. This study indicates that the  highest variability in Sea Surface Salinity (SSS) is found near the mouths of the major  rivers, such as the Ganges-Brahmaputra-Meghna (GBM) in the northern BoB and the  Irrawaddy in the northern Andaman Sea. There's also notable variation along the western  boundary of the basin, though to a lesser extent. The results show a large increase in  surface salinity along the Bangladeshi coast especially in the eastern part in near future,  which may affect the area of fresh water plume-suggesting that variations in river flow  can significantly influence the dynamic marine ecosystems of the northern BoB during  the time period between 2016 and 2020. These modifications are anticipated to cause  considerable alterations in the coastal aquatic ecosystems in coastal areas. J. of Sci. and Tech. Res. 6(2): 65-75, 2025